Persepsi Dosen terhadap Faktor-Faktor yang Mempengaruhi Kepuasan Kerja di Universitas Swasta - Wartono, Tono (LPPM UNU CIREBON, 2024)
Lecturer job satisfaction is an important factor in creating a conducive and high-performance academic environment. In private higher education environments, lecturers often face complex challenges, such as high workloads, inadequate reward systems, and limited access to career development. This study aims to explore lecturers' perceptions of the factors that influence their job satisfaction. This study uses a descriptive qualitative approach, with data collection techniques through semi-structured interviews with six teen lecturers from various study programs at a private university in Cirebon city. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions using thematic analysis techniques. The results of the study indicate that lecturer job satisfaction is influenced by several main factors, namely support from leaders, clarity of workload, fair compensation system, opportunities for self-development, and good social relations between colleagues. In addition to structural factors, psychological aspects such as recognition, appreciation, and a sense of belonging to the institution also determine the level of job satisfaction. These findings emphasize that human resource management in private higher education environments needs to accommodate lecturers' needs holistically, not only in financial aspects but also in professional and emotional dimensions. This study provides strategic recommendations for campus management in formulating more participatory HR policies that are oriented towards lecturer welfare.